2016
DOI: 10.1523/jneurosci.0174-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cells in Neuromuscular Junction Formation and Maintenance

Abstract: The neuromuscular junction (NMJ) is a tripartite synapse that is formed by motor nerve terminals, postjunctional muscle membranes, and terminal Schwann cells (TSCs) that cover the nerve-muscle contact. NMJ formation requires intimate communications among the three different components. Unlike nerve-muscle interaction, which has been well characterized, less is known about the role of SCs in NMJ formation and maintenance. We show that SCs in mice lead nerve terminals to prepatterned AChRs. Ablating SCs at E8.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 95 publications
4
71
0
1
Order By: Relevance
“…Skeletal muscle function is also intimately related to neuromuscular junction (NMJ), and NMJ consists of presynaptic nerve terminal, postsynaptic muscle fiber rich in acetylcholine receptors, and terminal Schwann cells (TSC; or perisynaptic Schwann cells ). Terminal Schwann cells (nonmyelinating SCs) have been reported to be an integral and essential component of NMJ, and several studies have reported that TSCs play an important role in the development, function, maintenance, and regulation of NMJs . Terminal Schwann cells are dynamic after acute nerve injury, and cytoplasmic processes from TSCs serve as platforms for axonal growth and nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle function is also intimately related to neuromuscular junction (NMJ), and NMJ consists of presynaptic nerve terminal, postsynaptic muscle fiber rich in acetylcholine receptors, and terminal Schwann cells (TSC; or perisynaptic Schwann cells ). Terminal Schwann cells (nonmyelinating SCs) have been reported to be an integral and essential component of NMJ, and several studies have reported that TSCs play an important role in the development, function, maintenance, and regulation of NMJs . Terminal Schwann cells are dynamic after acute nerve injury, and cytoplasmic processes from TSCs serve as platforms for axonal growth and nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal Schwann cells (nonmyelinating SCs) have been reported to be an integral and essential component of NMJ, and several studies have reported that TSCs play an important role in the development, function, maintenance, and regulation of NMJs. 36,[56][57][58][59][60][61][62][63] Terminal Schwann cells are dynamic after acute nerve injury, and cytoplasmic processes from TSCs serve as platforms for axonal growth and nerve regeneration. Terminal Schwann cells also modulate activitydependent neurotransmitter release and neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Exemplifying this point, the loss of the presynaptic or postsynaptic site in adulthood resulting from diseases and injuries causes the NMJ to degenerate [59]. The NMJ fragments and malfunctions within a few days after Schwann cells, including PSCs, are ablated [60]. Conversely, these three cellular components collaborate through synapse-associated molecules to regenerate adult NMJs following injuries that cause severing of motor axons, loss of PSCs and atrophy of muscle fibers [27].…”
Section: Lifestyle and Molecular Factors That Preserve The Nmj Intmentioning
confidence: 99%
“…Given the ability of tSCs to influence nerve growth and their location at the endplates of developing muscles, investigators have been interested in whether tSCs might play a role in synapse elimination [12,26,27]. Smith et al [27] conducted a detailed light and electron microscopic study of this issue.…”
Section: Tscs Are Active During Developmental Synapse Eliminationmentioning
confidence: 99%